L’atome Dans Le Manuel Scolaire De L’enseignement Secondaire Au Maroc - M., Ben mesaoud,; M., Belfazga; M., Radid; M., Dakkach; R., Janati-Idrissi; M., Madrane (European Scientific Journal, ESJ, 2018)
Textbooks play a significant role in the teaching-learning process as a result of didactic transposition, and as a vehicle employed for institutional learning. This descriptive study is devoted to conducting a thematic didactic analysis of textbooks of physics and chemistry of the common core of science and technology of secondary education in Morocco on the subject of atom. This paper focuses on contributing to the treatment of one of the problems that deals with the didactic transposition of the scientific concepts related to the "atom", in order to detect the different problems that can hinder their teachinglearning process. At the methodological level, we used a specific prior grid applied to the same theme. This allowed us to draw a hypothesis on the possible effect of the didactic presentation of concepts related to the atom in understanding the students. It also aim to propose recommendations to remedy the imbalances observed; such as: the dissymmetry between textual and figurative aspects, the absence of analogy, the problem of modeling, and the upgrading between objectives, contents, and proposed activities, etc.